The Role of Health Anxiety among Patients with Chronic Pain in Determining Response to Therapy - Heather D Hadjistavropoulos; Gordon JG Asmundson; Diane L LaChapelle; Allisson Quine (Pain Research and Management)
Considerable research suggests that health anxiety (HA) influences the response of patients with chronic pain to pain and treatment. The present investigation extends the current understanding of HA and explores whether it affects how patients respond to a common therapeutic intervention, namely instructions to reduce pain behaviour. Sixty-five patients with chronic pain completed measures of pain, anxiety and cognition following an active occupational therapy session in which they were specifically instructed either to inhibit or reduce pain behaviour, or to carry out the session as they normally would. Regression analyses revealed that those with higher levels of HA experienced greater anxiety, somatic sensations and catastrophic cognitions during therapy than those with lower levels of HA. The regression analyses also revealed a consistent trend for an interaction between HA and instructional set; when those with higher HA reduced their pain behaviour, they subsequently reported greater anxiety, and more somatic sensations and catastrophic thoughts than when they carried out the session as they normally would. In contrast, only those with lower HA had a tendency to benefit from reducing pain behaviour, reporting lower state anxiety and fewer somatic sensations during the session than those who did not reduce their pain behaviour. The results suggest that HA should be taken into consideration during treatment.